Perioperative Management of Patients with Ventricular Septal Defect, Severe Tricuspid Regurgitation and Gerbode Defects - Purwoko Purwoko; Ardhana Surya Aji (Solo Journal of Anesthesi, Pain and Critical Care (SOJA), 2021)
Ventricular Septal Defect (VSD) is a congenital heart disease that causes the connection between left and right ventricles called a Gerbode defect. Manifestation of a Gerbode defect is damage to the opening tricuspid valve caused regurgitation of the tricuspid valve. Delay in diagnosis and intervention will affect pre-operative nutritional status and malnutrition.We reported a boy aged 2 months, weighing 3100 grams with biliary atresia followed by VSD, severe TR, and Gerbode defect who will undergo the Kasai procedure. Preoperative physical examination showed GCS E4V5M6, SpO2 100%. The skin gets icteric all over the body and conjunctiva. The cardiovascular system has a regular I-II heart sound, 2/3 mid clavicular S noise as high as 2 ICS and a pansystolic murmur. The examination of the abdomen is slight distended. Child pug score 8. Hemoglobin value 6.7gr%, hematocrite 37%, APTT 44.8 seconds, SGOT 443 U / L, SGPT 560 U / L, total bilirubin 23.89 mg / dl, direct bilirubin 13.92 mg / dl, and indirect bilirubin 9.97 mg / dl.The goal of anesthesia in VSD, Severe Tricuspid Regurgitation (TR) with Gerbode Defect is preventing excessive ventilation to avoid severe pulmonary hypertension. The choice of anesthetic agent is based on the patient's physiology and balancing pulmonary and systemic blood flow. Perioperative management of cases of VSD, TR Severe with Gerbode defect in the following report describes the importance of understanding the pathophysiology of VSD and Gerbode defects to obtain a good outcome.Perioperative management of VSD patients, severe tricuspid regurgitation with Gerbode defect requires more supervision, especially to minimize the increase in PVR, maintain systemic vascular resistance (SVR) and avoid excessive ventilation to prevent severe pulmonary hypertension.